1984
DOI: 10.1002/1097-0142(19841001)54:7<1418::aid-cncr2820540731>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Pleural plaques and risk of cancer in Turin, Northwestern Italy. An autopsy study

Abstract: The relationship between the occurrence of neoplastic diseases and the presence of pleural plaques was studied in a series of 1097 autopsies performed in Turin from the adult general population. In men, pleural plaques showed an association with the presence of laryngeal, pulmonary, esophageal, and colorectal cancer. Only cancer of the larynx was strongly related to the occurrence of such pleural changes. This autopsy investigation confirms previous observations by others based on x‐ray findings, and suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…10 Thus, even if the development of pleural plaques is an entirely independent process from the development of malignant effects, such as lung cancer or mesothelioma, it is likely that there will be a correlation between pleural plaques and other serious endpoints, including lung cancer or mesothelioma. Several studies (Bianchi et al, 1997;Cullen et al, 2005;Cvitanović et al, 2003;Edge, 1976;Fletcher, 1972;Hillerdal, 1994;Karjalainen et al, 1999;Liddell & McDonald, 1980;Mollo et al, 1984;Sandén et al, 1992;Sheers, 1979) have shown that subjects with pleural plaques have a greater 9 This is presumably meant as a statistical fact; pleural plaques are also associated with exposure to other materials. As noted by Sargent et al (1978): ''Although asbestos dust inhalation is not the sole cause of pleural plaques, it is certainly the most common''.…”
Section: Pleural Plaques As Markers Of Exposurementioning
confidence: 99%
“…10 Thus, even if the development of pleural plaques is an entirely independent process from the development of malignant effects, such as lung cancer or mesothelioma, it is likely that there will be a correlation between pleural plaques and other serious endpoints, including lung cancer or mesothelioma. Several studies (Bianchi et al, 1997;Cullen et al, 2005;Cvitanović et al, 2003;Edge, 1976;Fletcher, 1972;Hillerdal, 1994;Karjalainen et al, 1999;Liddell & McDonald, 1980;Mollo et al, 1984;Sandén et al, 1992;Sheers, 1979) have shown that subjects with pleural plaques have a greater 9 This is presumably meant as a statistical fact; pleural plaques are also associated with exposure to other materials. As noted by Sargent et al (1978): ''Although asbestos dust inhalation is not the sole cause of pleural plaques, it is certainly the most common''.…”
Section: Pleural Plaques As Markers Of Exposurementioning
confidence: 99%
“…A review of the 1966-1992 English-language literature to assess the potential links between asbestos-related pleural plaques and lung cancer in the absence of asbestosis was published in 1993 [34]. Of 13 identified studies, six were cohort studies [18,[35][36][37][38][39], four were case-control studies [37,[40][41][42], and three were autopsy studies [43][44][45]. Only three studies, including two cohort studies in shipyard workers [35,36] and one casecontrol study [40], suggested an increased lung cancer risk in individuals having radiographic evidence of pleural plaques.…”
Section: Pleural Plaques and Lung Cancermentioning
confidence: 99%
“…Parnes and Sherman 10,11 agreed with this observation. Mollo et al ., 12 while exploring the relationship of neoplastic disease and pleural plaques in post‐mortem specimens, found a strong association for the presence of pleural plaques with laryngeal malignancy. Their work does not imply causation.…”
Section: Cross‐sectional and Post‐mortem Studiesmentioning
confidence: 99%